Algunos aspectos jurídicos del cifrado de comunicaciones - Álvarez Valenzuela, Daniel (2019)
This work explores some of the most relevant legal considerations on the relationship between encryption of private communications and some constitutional rights, with a focus on Chilean law. We maintain that there is an unresolved tension in the role of the use of communications encryption tools with respect to the exercise of these fundamental rights and public security. To do this, after briefly introducing the concept of encryption, we review the bases of the regulatory debate in the United States, essentially contained in its rules on intelligence and export control of encryption tools, and synthetically review the American constitutional debate. Regarding the European Union, we identify the main legal and political elements that are influencing the community’s pre-regulatory debate. Next, the main legal aspects involved in the use of encryption tools are characterized.